Is there Really a When-Issued Premium? - John R. Ezzell; James A. Miles; J. Harold Mulherin (Claremont McKenna College, Department of Economics, 2001)
We use a unique set of equities in the when-issued market to provide new tests of the law of one price in financial markets. We compare the prices of when-issued and regular-way shares of publicly-traded subsidiaries and their parents around the time the subsidiaries are fully divested. In contrast to prior analyses of when-issued trading in equity markets, we find that the when-issued shares of the subsidiary trade at a discount. Some of the pricing differences stem from measurement factors such as exchange location and bid-ask clustering that bias the observed when-issued pricing differential away from zero. The remaining difference between the when-issued and regular-way prices is due to asymmetric movements in bid and ask quotes in the two markets. We also find evidence of temporary price pressures on the date of execution of the spinoff of the subsidiary firms that bear resemblance to the pricing in the when-issued market. We interpret the evidence as consistent with the law of one price in the presence of transaction costs.
Keywords: 330; Law of One Price; Market Efficiency; Market Microstructure